Fulfilling the Subsistence of a Convict Husband from the Perspective of Islamic Law and Positive Law in the Palu City Religious Court - muhaimin, alif; Marzuki, Marzuki; M.Taufan; Suhri Hanafi (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2024)
This article is related to fulfilling the livelihood of a convict husband from the perspective of Islamic law and positive law in the Class II A correctional institution Palu. So the research aims are (1) To find out the efforts to fulfill the livelihood of husbands with convict status while in the Class II A correctional institution Palu. (2) To find out the fulfillment of convicts' husbands from the Islamic Law and Positive Law perspective in the Class II A correctional institution Palu. This research uses qualitative methods with data collection techniques: observation, interviews, and documentation. Researchers use data analysis techniques, such as data reduction, presentation, verification, and conclusion. Research results: (1) The maintenance obligations of husbands with convict status were implemented, less implemented, and not implemented.